EDUKASI EVAKUASI GEMPA BUMI SEBAGAI MITIGASI BENCANA DI SMK AD-DA’WAH - Tommy IDUWIN; Pratiwi Setyaning Putri; Dicki Dian Purnama; Tri Yuhanah (Sekolah Tinggi Teknik - PLN, 2019)
Abstract SMK Ad Da’wah which is located at Duri Kosambi, Cengkareng, Jakarta Barat is one of many school that is affected earthquake impact in 2018. After earthquake on January 2018, there is no information about evaquation procedure during earthquake at school. Preparedness due to earthquake disaster also not integrated into their syllabus. Education activity method applied by using illumination and demonstration about evacuating during the earthquake disaster. It will be applied involve PKM’s team and SMK Ad Da’wah’s students. The speaker came from Department of Civil Engineering STT PLN Duri Kosambi, Cengkareng, Jakarta Barat. It will be supported by the school itself too. Funds are supported by STT PLN that is an important aspect in the implementation of these activites. PKM activities are expected to bring the comprehension of the significant earthquake evacuation. It expected could reduce casualties and damage caused by the earthquake disaster. Keywords: Earthquake, Evacuation, Casualties